Structural integrity of lithium-ion pouch battery subjected to three-point bending. (August 2022) - Arief Budiman, Bentang; Rahardian, Samuel; Saputro, Andy; Hidayat, Arif; Pulung Nurprasetio, Ignatius; Sambegoro, Poetro
Highlights: The role of pouch battery configuration to the battery structural integrity is revealed. Experimental and numerical analyses of three-point bending test were conducted for different configuration. Representative Volume Element (RVE) model of the pouch battery is introduced to investigate stress and deformation inside the battery. The failure mechanisms of the battery using folded configuration and aluminum foil casing are discussed. Abstract: The role of pouch battery configurations in structural integrity under bending loads was investigated using finite elements and compared with experiments. Three-point bending tests were firstly conducted for different pouch battery configurations to obtain force–displacement curves. A finite element model of the pouch battery under the three-point bending was then simulated employing a homogenization technique to reduce the simulation cost and time consumption significantly. Force-displacement curves from the simulation results were extracted and validated by the curve obtained from the bending tests. The validation allowed detailed analysis of stress distribution and deformation inside the pouch battery model. Regions in which short circuits might occur were then identified. The role of folded configuration and pouch casing to resist flexural damage was confirmed by structural strength improvement of 14 and 30 times, respectively. These results may be used for design consideration on safer pouch batteries.